Proposal of a new research construct in female entrepreneurship - Vadnjal, Mateja (Array, 2020)
Entrepreneurship has been a gender-defined phenomenon for several decades. It has been presented as a typically male domain which for its demanding performance requires typical male characteristics. In this paper, we follow the suggestions of researchers of female entrepreneurs and focus on the research of three groups of female entrepreneurs. We propose that female entrepreneurs in different life stages have distinguished forms of human and social capital, and we apply the factors of those capitals to be measured. We observe the influence of parents, maternity as a metaphor for family involvement and family responsibilities, friends, and the broader environment on social capital. We discussed female entrepreneurship using two functions - as emotional support and incentives and as an instrumental social capital that provides access to information, resources and business partners. We added previous entrepreneurial experience, the level of education attained, business knowledge acquired at school and specific training, industry experience, previous managerial experience to the human capital function. With our model, we introduced the theory of life expectancy of women into entrepreneurship theory, which brings us closer to understanding the external influences on entrepreneurial aspirations and motivations of women of different ages.